Development of self-guided tour ecotourism Bandung Regency - Distria, Tiara Fadila; Septyandi, Chandra Budhi; Nugraha, Azizah Salsabila; Susanto, Eko (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The development of ecotourism in the South Bandung Region has empirically impacted nature and society. To overcome the negative impacts of these developments, efforts are needed to educate tourists about the protection of nature and society and the purpose and principle of sustainable ecotourism development. This article contains the process of designing a guidebook for self-guided ecotourism tours in South Bandung to support sustainable tourism management in the region. By involving 134 South Bandung tourist respondents, this design has successfully applied the Technology Acceptance Model theory as a design platform. The results of this design in the form of a travel guidebook are expected to be widely used by stakeholders and become empirical evidence of the application of TAM as a framework for designing the latest travel guidebook